Complexity, Clarity, and Earnings Management: The Impact of Financial Report Obfuscation on Investor Perception and Stock Valuation - Ngadi Permana; Farah Qalbia; Eri Kusnanto (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
This qualitative literature review explores the relationship between financial report obfuscation, complexity, transparency, and earnings management, focusing on how these factors influence investor perception and stock valuation. The review examines the strategic manipulation of financial reports by managers, specifically through obfuscation techniques that distort financial transparency. Obfuscation, by disaggregating financial data into numerous line items, can exacerbate biases in reported profitability, leading investors to extrapolate distorted valuations. This paper reviews the interplay between complexity and transparency in financial reporting and its implications for earnings management. It highlights the challenges investors face in interpreting complex financial reports, leading to potential misvaluation of firms. The review also considers how various factors, such as investor sophistication and managerial honesty, affect the degree of obfuscation and earnings management.